Frequency of Stroke Acquired Pneumonia in Patients Admitted in Intensive Care Unit with Stroke - Kiran Shahzadi, Shafaq Mannan, Muhammad Ahmad (Pakistan Journal of Medical & Health Sciences, 2022)
Introduction: Stroke is a highly morbid entity, and it can be fatal directly due to neurological damage and affecting the respiratory system or can add to overall morbidity and mortality due to its associated complications like stroke-associated pneumonia (SAP). Objective: The objective of this study was to investigate the prevalence of stroke-associated pneumonia in ICU patients. Study Design: This Descriptive case series was conducted in Saddique Family Hospital Gujranwala from October 2020 to April 2021. In this study, the cases of either gender agaged0 to 70 years suffering from stroke within 12 hours were included. SAP was labels on fever, cough, and non-homogenous opacities on chest X-ray. Results: In the present study, 160 cases of stroke were included, and out of these 82 (51.25%) were males and 78 (48.75%) females. The mean age of the subjects was 54.24±7.15 years and the mean duration of stroke was 7.05±2.54 hours. There were 35 (21.88%) cases that had DM, 28 (17.50%) had HTN and 30 (18.75%) of cases had a history of smoking. In 20 (12.50%) of the patients, stroke-acquired pneumonia (SAP) was discovered. With a p= 0.34, SAP was found in 12 (15.38%) female patients compared to 8 (9.75%) male cases. With a p= 0.15, SAP was more common in instances with DM, where it was detected in 7 (20%) of the cases compared to 13 (10.4%) in cases without DM. SAP was found in 5 (17.85%) instances of HTN and 4 (13.33%) cases of smoking history, with p values of 0.35 and 1.0, respectively. SAP was found in 15 (14.42%) patients with a stroke length of 6-12 hours, compared to 5 (8.92%) instances with a stroke duration of shorter than this, with a p= 0.45. Conclusion: Stroke acquired pneumonia is not uncommon and is seen in more than 1 out of every 10 cases and it is more seen in females and those with history of DM, HTN and duration of stroke 6 to 12 hours, though none of this variable was found statistically significant.